Investigation and Identification of let-7a Related Functional Proteins in Gastric Carcinoma by Proteomics - Yimin Zhu; Xingyuan Xiao; Lairong Dong; Zhiming Liu (Analytical Cellular Pathology)
MicroRNAs are small noncoding RNA molecules that control expression of target genes. Our previous studies show that let-7a decreased in gastric carcinoma and that up-regulation of let-7a by gene augmentation inhibited gastric carcinoma cell growth both in vitro and in vivo, whereas it remains largely unclear as to how let-7a affects tumor growth. In this study, proteins associated with the function of let-7a were detected by high throughout screening. The cell line of SGC-7901 stablely overexpressing let-7a was successfully established by gene cloning. Two-dimensional gel electrophoresis (2-DEy was used to separate the total proteins of SGC-7901/let-7a, SGC-7901/EV and SGC-7901, and PDQuest software was applied to analyze 2-DE images. Ten different protein spots were identified by MALDI-TOF-MS, and they may be the proteins associated with let-7a function. The overexpressed proteins included Antioxidant protein 2, Insulin–like growth factor binding protein 2, Protein disulfide isomerase A2, C-1-tetrahydrofolate synthase, Cyclin-dependent kinase inhibitor1 (CDKN1) and Rho–GTPase activating protein 4. The underexpressed proteins consisted of S-phase kinase-associated protein 2 (Spk2), Platelet membrane glycoprotein, Fibronectin and Cks1 protein. Furthermore, the different expression levels of the partial proteins (CDKN1, Spk2 and Fibronectin) were confirmed by western blot analysis. The data suggest that these differential proteins are involved in a novel let-7a signal pathway and these findings provide the basis to investigate the functional mechanisms of let-7a in gastric carcinoma.